MiR-199a-5p regulates rat liver regeneration and hepatocyte proliferation by targeting TNF-α TNFR1/TRADD/CASPASE8/CASPASE3 signalling pathway. Issue 1 (4th December 2019) - Zhang, Chunyan; Ye, Bingyu; Wei, Jiaojiao; Wang, Qiwen; Xu, Cunshuan; Yu, Guoying
Abstract: Abnormally expressed miR-199a-5p (miR-199a) has been frequently reported in multiple types of malignancies. Nevertheless, its effect in liver regeneration (LR) is largely still unclear. Herein, we investigated the function of miR-199a in hepatocyte proliferation during LR. As a result, miR-199a expression was significantly increased 12–30 h, in rat hepatic tissue, after partial hepatectomy (PH). The down-regulated expression of miR-199a inhibited proliferation as well as promoted cell apoptosis of BRL-3A. Additionally, TNF-α was found as a target of miR-199a. The administration of TNF-α siRNA regulated the effects of miR-199a on hepatocyte proliferation as well as miR-199a-modulated TNF-α/TNFR1/TRADD/CASPASE8/CASPASE3 signalling pathways. Taken together, these present findings suggested that miR-199a promoted hepatocyte proliferation as well as LR via targeting TNF-α/TNFR1/TRADD/CASPASE8/CASPASE3.